ANALYSIS OF THE INFLUENCE OF READING INTEREST ON THE LEARNING ACHIEVEMENT INDEX OF FKIP UNVERSITY STUDENTS PGRI PALANGKA RAYA for 2014/2015 ACADEMIC YEAR - Akhmad syarif (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
The sentence was clearly no stranger become the credo (belief, belief) that fill the various spaces of enlightenment in our country. Unfortunately, we have imbelitty that was very severe. Thousands of creed, slogan, motto lined up, all just be come such kind of. Akan but reading is a necessity. By reading one can obtain a variety of information needed, stimulated creativity, encourage the emergence of a desire to be able to think critically and systematically, expanding and enriching as well as forming a superior personality and competitive. Behavior of FKIP of students PGRI University of Palangkaraya is various some of hem who read when lecture comes and some of them who read at home, or anyone read through the discussion but this activity is almost never done. More students choose to chat with their friends while waiting the Lecturer or elsewhere than on bringing the books and reading. Therefore, the researcher intends to know how to influence student interest in reading education building techniques to GPA for one semester. The results showed that there is a relationship (correlation) between the interest in reading and the students’s Achievement Index (IP).